The Mechanical Properties of in Situ Canine Skeletal Muscle - Allen, P. D.; Barclay, J. K. (Frontiers in Physiology, 2022)
This study was undertaken to determine if fiber arrangement were responsible for differences in the whole muscle mechanical properties. Experiments were carried out in situ in blood perfused muscles at approximately normal body temperature between 36o and 38oC. The following mechanical relationships were studied: 1.) Length:Tension; 2.) Force:Velocity; and 3.) Stress:Strain of Series Elastic using a pneumatic muscle lever to measure Tension (P), length (L), dP/dt and dL/dt using a high frequency oscillograph (500-1000Hz). Electron microscopy and fiber typing were done as adjunctive studies. Muscles were stimulated by direct nerve stimulation with 0.1msec stimuli at a rate of 1 impulse per second for twitch contractions, or in 200 msec bursts of 0.1msec 100Hz stimuli for brief tetanic contractions. The pennate short fibered gastrocnemius plantaris developed 1.0 kg/g of tension during brief tetanic stimulation, at optimal length (Lo) with full stimulus voltage, while the parallel long fibered semitendinosus developed 0.5kg/g under the same conditions. The Length:Tension relationship for these two muscles was qualitatively similar but quantitatively different. The Force:Velocity relationship (deltaL/L0 vs P/P0 ) for both muscles were also qualitatively similar and could be described by the previously proposed rectangular hyperbola but a better predicted fit to the observed data could be produced by adding a descending exponential function to the rectangular hyperbola. Unlike previous studies, the Stress:Strain properties of the series elastic component measured by quick release (deltaL/Li vs deltaP/Po) were linear and gastrocnemius was 25 per cent higher than the semitendinosus. Overall, both muscles were found to have mechanical properties that differed little from the previously reported literature for amphibian, cardiac and small mammalian muscles studied by others in vitro. The major differences that we found were in the shapes of the force:velocity curve of the contractile component, and the Stress:Strain curve of series elastic component. Equations and explanations for these differences are devised and presented.